Innovative forms of capacity building in the public administration – the example of the “CaPABle” project - Michał Ślusarczyk (Edukacja Ustawiczna Dorosłych)
This article describes the results of the work of an international consortium within the CAPABLE project – on building the competence of public administration staff involved in the renovation of their building stock. The main outcome of this work is the creation of an innovative competence tool in the form of an innovative e-learning platform, a competence handbook and the publication of recommendations for central and local authorities to overcome barriers to the implementation of green building in public administration. All data included in the article are from the project’s internal resources and are presented on the basis of our own research. These data indicate that there is a need for innovative and customised knowledge enhancement tools, particularly in the context of the specifics of public administration employees.